INTERFERENCE MITIGATION FOR UNDERLAY COGNITIVE RADIO SYSTEM - Meylani, Linda
The limitation of available resources and increasing the need of accessing resources make Cognitive Radio (CR) system and non-orthogonal multiple access (NOMA) as one of solutions to increase user connectivity especially in 5G and 6G communication systems. In underlay cognitive radio scheme, Primary User (PU) and Secondary User (SU) are allowed to transmit simultaneously with certain requirements, where the total interference caused by SU must be below the interference limit. Cognitive radio plays a role in controlling and mitigating interference. On this dissertation, the cognitive radio communication system is evaluated with Low Density Signature Orthogonal Frequency Division Multiplexing (LDSOFDM). LDS-OFDM is a code domain NOMA, where all users spread their data using non-orthogonal codes. Due to the non-orthogonality of the spreading codes, LDS–OFDM can increase the number of accessing users, and can apply message passing algorithm (MPA) as its decoder. MPA’s performance is closer to that of the optimum detector, however the complexity will increase along with the increasing number of users. This dissertation research proposes interference mitigation techniques in the underlay CR system by using LDS–OFDM as a multiple access scheme. Interference mitigation has been done in two schemes i.e. resource allocation management for SU by taking into account the fairness metric (FM), and multi-user detection (MUD) with low complexity by using Peeling Decoding (PD) combined with Selection Combining (SC) and Maximum Ratio Combining (MRC). Interference Limit Resource Allocation based on Fairness Metric (ILRA-FM) algorithm is proposed to confine number of SU to access one resource based on dc parameter, interference limit, and fairness in the number of resources obtained for each SU. The proposed algorithms work based on two parameters, i.e. number accessing user in a resource, dc, and Signal to Noise Ratio (SINR). The computer simulation is used to know the performance of the proposed algorithm. User’s positions are generated randomly and used COST–231 Walfisch Ikegami as pathloss model. The performance parameters are indicated by outage probability (OP), the average throughput, Fairness Metric (FM) and Fairness Index (FI). The simulation results show that ILRA–FM type 1 and ILRA–FM type 2 has lower outage probability than ILRA, however the OP value is higher than Round Robin (RR) algorithm. iiiThe proposed algorithm, ILRA–FM type 1 and ILRA–FM type 2 have higher value of fairness metric (FM) rather than ILRA and RR algorithm especially when the number of SU in the system is quite large. MUD technique using PD–SC and PD–MRC is designed by taking into account the allocation of different power for each SU in each resource. PD-SC and PD– MRC has lower complexity than MPA. The simulation results show that the performance of all users are affected by the value of Rgap. Joint combination of power weight and the proposed decoding algorithm PD–SC and PD–MRC ave a better performance compare with the multiple domain non–orthogonal multiple access, Pattern Division Multiple Access (PDMA) with successive interference cancellation. The proposed detection algorithm has a better performance rather than the MPA algorithm for downlink transmission, which is indicated by smaller bit error rate (BER) value.